2019
DOI: 10.1002/ieam.4187
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Seafood and Vegetable Production: Aquaponics as a Potential Opportunity in Urban Areas

Abstract: Global population growth will increase pressures on current food systems in order to supply adequate protein and produce to the increasingly urban world population. The environmental impact of food production is a critical area of study as it influences water and air quality, ecosystem functions, and energy consumption. Aquaponics (in which seafood and vegetables are grown in a closed‐loop system) has the potential to reduce the environmental impact of food production. A review of the current environmental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 128 publications
0
17
0
Order By: Relevance
“…Conversely, there were also a few articles that only mentioned food systems superficially but had a breadth of research in terms of number of components and relationships. For example, Wu et al.’s (2019) study on sustainable seafood and vegetable production evaluated innovations through aquaponics, environmental and economic sustainability impacts, demographic (urban) drivers, and implications for diets, food safety, and human health, but food systems was only mentioned once. Whilst our review deliberately focussed on those studies that invoked the term food systems, we don't argue that is a necessary attribute of good, useful or impactful research on food systems.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there were also a few articles that only mentioned food systems superficially but had a breadth of research in terms of number of components and relationships. For example, Wu et al.’s (2019) study on sustainable seafood and vegetable production evaluated innovations through aquaponics, environmental and economic sustainability impacts, demographic (urban) drivers, and implications for diets, food safety, and human health, but food systems was only mentioned once. Whilst our review deliberately focussed on those studies that invoked the term food systems, we don't argue that is a necessary attribute of good, useful or impactful research on food systems.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to environmental sustainability, many studies evaluated the environmental impacts of aquaponics (Bohnes et al, 2018;Cohen et al, 2018;Kalvakaalva, 2020;Maucieri et al, 2018;Somerville et al, 2014;Song et al, 2019;Wu et al, 2019). Cohen et al (2018) found that combined aquaponic fish-vegetable production would result in significant reduction of impacts in eutrophication, water intake (water use), and geographic footprint (land use) environmental impact categories, compared to large-scale traditional non-integrated production (Cohen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The investigated impacts usually only cover a limited subset of the relevant environmental impact categories (Bohnes & Laurent, 2019;Wu et al, 2019); (b) the investigated systems are predominantly located in warm weather locations, in which heating and lighting requirements are relatively lower; and may not be representative to cold weather locations, in which heat requirements are relatively high (Wu et al, 2019); and (c) applied alternatives to mitigate the environmental impacts of aquaponics are not fully explored within the studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dal Bo Zanon et al 2017), rooftop production(Sanjuan- Delmás et al 2018;Toboso-Chavero et al 2019;Salvador et al 2019), or urban aquaponics(Wu et al 2019).…”
mentioning
confidence: 99%